HUBUNGAN KUALITAS KERJA SAMA SEKOLAH DAN ORANG TUA DENGAN INTENSITAS USAHA BELAJAR SISWA DI SMP NEGERI KOTA TASIKMALAYA - Mumu, Mumu; Majid, A; Rohyana, Aang (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2019)
The purpose of this research is to know the effort of school to cooperate with parents, form of cooperation between school with parents of student barrier in cooperation and effort of school overcome barrier in cooperation. The research method used is descriptive research and quantitative data analysis of data collection using survey research method. The subject matter of this research is the involvement of parents and the school in education. The results revealed not all parents can be automatically involved in school. Therefore, the school should take steps or initiatives to seek cooperation with parents to achieve the goal of child education which are: Climate quality of school cooperation with the community, parent willingness to get involved, Form of cooperation between schools and parents. Cooperation is important in order to continuous process in stimulating the development of children either from school to home or vice versa, it is done school efforts to cooperate with parents, that is creating a comfortable school climate, making initial communication with parents, and providing opportunities for parents to be involved, between parent school, communication, volunteer, parent involvement in child study at home, and collaboration with community group. Obstacles in cooperation between school and parents are differentiated into two factors: internal and external factors. Internal factors include teacher beliefs, teacher's views on parents, and teacher constraints. External factors include parental views, life demands, and parental attitudes. School efforts to overcome barriers in cooperation with parents is to find a variety of communication methods and find the right time for parents to be present in school events